A Microcontroller Implementation of Harmonic Control Arrays Method - (:unkn) unknown (IEEE, 2017)
Harmonic Control Arrays (HCA) is a method based on adjusting the harmonic components of the control signal to minimize the error signal for systems with periodic references and disturbances. In this study the results of a discrete-time implementation of HCA with a microcontroller as the control unit has been represented. A low-pass filter (LPF) and a nonlinear electronic circuit has chosen as the plant, and a periodic sinusoidal reference signal have been applied on it.
Keywords: nonlinear signal processing; signal processing hardware; discrete time control